PENGARUH TALENT MANAGEMENT DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PT. AGRO MUKO BUNGA TANJUNG ESTATE - Nopela Liswanti; Mimi Kurnia Nengsih (UM. Bengkulu, 2026)
This study aims to determine the effect of Talent Management and Career Development on Employee Performance at PT. Agro Muko Bunga Tanjung Estate. This study uses a quantitative approach with a survey method. The sample consisted of 154 respondents who are employees of PT. Agro Muko Bunga Tanjung Estate. Data collection was conducted through the distribution of questionnaires and analyzed using SPSS, including instrument testing, classical assumption testing, multiple linear regression, t-test, F-test, and determination coefficient. The results of the t-test hypothesis on the Talent Management variable showed t-calculated > t-table (14.922 > 1.976) and sig < a (0.00 < 0.05), the Career Development variable showed t calculated > t table (3.355 > 1.976) and sig < a (0.00 < 0.05). The results of the F test show that the calculated F value is 126.252 > F table 3.06 and sig 0.00 < 0.05. From the results of the study, it can be concluded that Talent Management and Career Development have a partial and simultaneous effect on the performance of employees at PT. Agro Muko Bunga Tanjung Estate. Keywords : Talent Management, Career Development, Employee Performance